OX40 costimulation can abrogate Foxp3(+) regulatory T cell-mediated suppression of antitumor immunity - Kitamura, Naomi (2009)
Regulatory T cells (Tregs) play an important role in maintaining immunological tolerance that is one of the main obstacles to overcome for improving antitumor immunity. Recently, the Treg has been shown to constitutively express OX40 (CD134), which is a member of the TNF receptor family that is transiently expressed on effector T cells after TCR triggering, and through which the signal enhances effector T cell proliferation and memory T cell development. However, little is known about the role of OX40 costimulation to Tregs in tumor immunology. Here we show that OX40 signaling modulates the function of naturally occurring Tregs in vitro and in vivo. Foxp3 expression on Tregs was reduced by OX40 costimulation, but not by IL-2 stimulation. Tregs suppressed the proliferation of naïve CD4(+) CD25(−) T cells after TCR triggering, in contrast, OX40 costimulated Tregs that reduced Foxp3 expression reversed the suppressive function. In addition, Tregs inhibited the proliferation of TCR stimulated (primed) CD4(+) T cells and naïve CD8(+) T cells after TCR-mediated activation, however, Tregs with OX40 costimulation lost their suppressive function. Interestingly, Tregs minimally suppressed the proliferation or the cytokine secreting of Ag-specific CD8(+) T cells after Ag-restimulation. Furthermore, Tregs suppressive function to the antitumor effect was reversed by OX40 costimulation in vivo. Our data indicate that, in addition to controlling effector T cell function, OX40 costimulation directly controls Treg-mediated suppression in tumor immunity.